A distinção analítico - sintético: um estudo comparativo entre Frege e Kant - Ferreira, Isaías Lima (2007)
This work aims to establish the comparison between Kant´s and Frege´s thoughts about the distinction between the analytical and synthetic judgments. Attention is drawn to the fact that there is not only one analyticity conception in the course of Kant´s philosophy. The central matter in this debate involves the nature of constitutive judgments of mathematics. Against Kantian position, according to which mathematics is based on synthetic a priori judgments, Frege´s thesis states that the analytical judgments are this science foundation. It is shown, however, favorable on accepting the same synthetic a priori judgments concerning geometry. This debate also includes the non Euclidean geometry and David Hilbert´s formalism that will play an important role as distinct positions Euclidean geometry conception which is shared by Kant and Frege